Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s00122-011-1708-3
|View full text |Cite
|
Sign up to set email alerts
|

A second ‘overexpression’ allele at the Glu-B1 high-molecular-weight glutenin locus of wheat: sequence characterisation and functional effects

Abstract: Bread is one of the major constituents of the human diet and wheat (Triticum aestivum L.) is the most important cereal for bread making. The gluten proteins (glutenins and gliadins) are recognised as important components affecting the processing quality of wheat flour. In this research, we investigated a particular glutenin subunit allele in an Australian cultivar, H45. Based on protein and DNA assays, the Glu-B1 allele of H45 seems to be Glu-B1al, an allele that includes a functional duplication of a gene enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…It is generally accepted that HMW-GS 5+10 can produce superior dough quality compared to 2+12 subunits (SARKAR et al, 2014). Possible reasons include the number and position of cysteine residues (WEEGELS et al, 1996;PIROZI et al, 2008), the accumulation rate differences during grain development (XU et al, 2006;GAO et al, 2012;LIU et al, 2012;WANG et al, 2013) and the formation of inter-or intra-molecular disulfide bonds which can stabilize the structure and increase the number of glutenin macropolymer (ALTENBACH et al, 2007;LAUDENCIA-CHINGCUANCO et al, 2007;SHEWRY et al, 2009;LI et al, 2010). Our results from this work further confirmed that CB037-B with HMW-GS 5+10 subunits has higher GMP content and better mixing property and breadmaking quality than CB037-A with 2+12 subunits (Table 1 and Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that HMW-GS 5+10 can produce superior dough quality compared to 2+12 subunits (SARKAR et al, 2014). Possible reasons include the number and position of cysteine residues (WEEGELS et al, 1996;PIROZI et al, 2008), the accumulation rate differences during grain development (XU et al, 2006;GAO et al, 2012;LIU et al, 2012;WANG et al, 2013) and the formation of inter-or intra-molecular disulfide bonds which can stabilize the structure and increase the number of glutenin macropolymer (ALTENBACH et al, 2007;LAUDENCIA-CHINGCUANCO et al, 2007;SHEWRY et al, 2009;LI et al, 2010). Our results from this work further confirmed that CB037-B with HMW-GS 5+10 subunits has higher GMP content and better mixing property and breadmaking quality than CB037-A with 2+12 subunits (Table 1 and Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al. () gave a plausible explanation for the weak strength of H45 by suggesting that the extra cysteine found in H45 sequences might act as a chain terminator. However, there is some evidence that in most cases, HMW glutenin subunits with extra numbers of cysteine residues are positively associated with improved processing quality in bread wheat varieties (Lafiandra et al.…”
Section: Discussionmentioning
confidence: 99%
“…In bread wheat it has been widely demonstrated that number of subunits in addition to the number and distribution of cysteine residues, available for intermolecular bonds, are responsible for differences of breadmaking quality of different wheat varieties, as also mentioned in the introduction. Results have been obtained that show that additional cysteines not always influence positively the bread-making quality of flour, as in the case of the 1Dx5 subunit [66][67][68]. On the basis of the rheological data obtained we can hypothesize that the additional cysteine present in the 1Ry subunit contributes to modulate differently the size distribution of glutenin polymers, producing a dough with a very large extensibility.…”
Section: Xym7mentioning
confidence: 94%